2018
DOI: 10.3389/fcimb.2018.00072
|View full text |Cite
|
Sign up to set email alerts
|

The CpxA/CpxR Two-Component System Affects Biofilm Formation and Virulence in Actinobacillus pleuropneumoniae

Abstract: Gram-negative bacteria have evolved numerous two-component systems (TCSs) to cope with external environmental changes. The CpxA/CpxR TCS consisting of the kinase CpxA and the regulator CpxR, is known to be involved in the biofilm formation and virulence of Escherichia coli. However, the role of CpxA/CpxR remained unclear in Actinobacillus pleuropneumoniae, a bacterial pathogen that can cause porcine contagious pleuropneumonia (PCP). In this report, we show that CpxA/CpxR contributes to the biofilm formation ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 52 publications
3
48
0
Order By: Relevance
“…Clearly the clinical serovar 8 WT strain showed the greatest adherence to all of the surfaces tested compared to the WT serovar 1 and reference strains, and deletion of hfq reduced adherence in all cases, but to different extents. These data support a role for Hfq in regulating at least some of the gene products contributing to adherence to the different surfaces in each of the serovar strains tested, but other regulators such as RpoE and H-NS (Bossé et al 2010) and the two component systems CpxA/CpxR (Li et al 2018) and QseA/QseB (Liu et al 2015) have also been shown to be involved, and their relative contributions to regulating this complex phenotype are unresolved.…”
Section: Discussionmentioning
confidence: 69%
“…Clearly the clinical serovar 8 WT strain showed the greatest adherence to all of the surfaces tested compared to the WT serovar 1 and reference strains, and deletion of hfq reduced adherence in all cases, but to different extents. These data support a role for Hfq in regulating at least some of the gene products contributing to adherence to the different surfaces in each of the serovar strains tested, but other regulators such as RpoE and H-NS (Bossé et al 2010) and the two component systems CpxA/CpxR (Li et al 2018) and QseA/QseB (Liu et al 2015) have also been shown to be involved, and their relative contributions to regulating this complex phenotype are unresolved.…”
Section: Discussionmentioning
confidence: 69%
“…The decreased capacity of the mutant strain to invade DF-1 cells might contribute to the inability of this mutant to effectively colonize, survive in and infect ducks. Similarly, decreased colonization and virulence have been observed for the cpx mutant strain in different Gram-negative pathogens [31, 6163].…”
Section: Discussionmentioning
confidence: 77%
“…A number of studies have documented the regulatory role of the CpxR in the synthesis of various bacterial appendages, including Pap pili [28], type IV bundle-forming pili [29,30], P pili [16], Longus [31], and flagella [32], all of which may subsequently affect the biofilm formation. Indeed, several studies have shown that CpxR has a direct [20,33] or indirect [34] role in the biofilm development. Although these studies have given us valuable information on the role of the CpxR on production of various appendages and/or provided information of the involvement of certain genes under CpxR control during biofilm formation, they still haven’t demonstrated an overall regulatory function of CpxR (i.e., regulon) associated with biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Several findings indicate that the Cpx response acts antagonistically to RpoE; specifically, repressing the production of outer membrane β-barrel proteins [17,18] and the σ E -induced chaperone Skp [19]. It has been established that the CpxR extracytoplasmic stress response regulator is important in the development of Actinobacillus pleuropneumoniae biofilms [20]. In this study, we examined individual and combined contributions of Cpx and RpoE to biofilm-associated phenotypes (i.e., auto-aggregation, swarming motility) as well as biofilm development in S .…”
Section: Introductionmentioning
confidence: 99%